2010
DOI: 10.1049/iet-its.2009.0028
|View full text |Cite
|
Sign up to set email alerts
|

Travel assistance device: utilising global positioning system-enabled mobile phones to aid transit riders with special needs

Abstract: Recent advancements in mobile technology allow global positioning system (GPS)-enabled cell phones to provide a variety of real-time location-based services. This study reports on the design, implementation and testing of such a service, the travel assistance device (TAD), that aids transit riders with special needs in using public transportation. TAD is a program that provides the rider with customised real-time audio, visual and tactile prompts for exiting the transit vehicle by announcing 'Get ready. . .' a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…The study isolates this effect while controlling for a wide variety of neighborhood-specific variables. Following a similar theme, Barbeau et al (2010) explored how new mobile apps enhance rider experience by providing real-time information about their trips, including alerting customers when to disembark or enabling riders to signal the driver to stop. Guo et al (2015) observed 1,739 passengers and surveyed 686 to evaluate usage patterns on the bus system in Vancouver, British Columbia.…”
Section: Relevant Literaturementioning
confidence: 99%
“…The study isolates this effect while controlling for a wide variety of neighborhood-specific variables. Following a similar theme, Barbeau et al (2010) explored how new mobile apps enhance rider experience by providing real-time information about their trips, including alerting customers when to disembark or enabling riders to signal the driver to stop. Guo et al (2015) observed 1,739 passengers and surveyed 686 to evaluate usage patterns on the bus system in Vancouver, British Columbia.…”
Section: Relevant Literaturementioning
confidence: 99%
“…Likewise, the Bluetooth-based application described in [13] ensures that the user is informed when a bus is arriving at a stop. The Travel Assistance Device (TAD) [2] and the app described by Silva et al [15] both rely on the GPS in the user's smartphone to determine the user's position and to alert the user when the bus is approaching the desired bus stop. Unlike this previous work, our system is designed from the ground up to assist users throughout the whole travel, from the time they arrive at the initial bus stop until they reach their destination.…”
Section: Related Workmentioning
confidence: 99%
“…The GPS Alarm Clock application ( Figure 7) is a novel application for travelers and public transit riders, similar to the accessibility application developed by Barbeau et al (2010), 41 to provide notification of proximity to a planned stop. This is targeted toward inattentive or sleeping passengers, as well as disabled travelers who need advanced warning of an approaching stop.…”
Section: Gps-enabled Dynamic Geocrowdsourcing Applicationsmentioning
confidence: 99%